Infusing Equity, Diversity and Inclusion (EDI) into Academic Integrity Practices in Canadian Higher Education - Chaudhuri, Anita; Lam, Anita; Spence, Kirsty; Rahimian, Matt (Canadian Perspectives on Academic Integrity, 2025)
Based on our experiences at four Canadian institutions of higher education, we contend that infusing EDI-informed language within academic integrity policy and procedures is important and should be supported by: (a) a transformative approach towards academic integrity that shifts from a “morality and rule compliance” framework (Penaluna & Ross, 2022); (b) asking questions such as, “what do we as instructors and institutions need to unlearn?” (McNeill, 2022) to cultivate belongingness and learning together about diverse systems and cultures of knowledge making (Davis, 2022); and (c) training students, staff, and instructors about ways to highlight aspirational aspects of integrity as well as diminishing anxiety ridden misconduct processes. Thus, to balance the maintenance of rigorous academic standards against the development of a more learning-centred culture of academic integrity, we believe EDI-informed best practices should be established at a system-level across multiple stakeholders responsible for different learning contexts. As a roadmap for structuring educative opportunities for students in such multiple teaching and learning contexts, we consider sites where revised practices might be most impactful, including: i) instructor-led classroom teaching; ii) administrator-led decision making and disciplinary processes; and iii) staff-led and student-centred programming, such as orientation, peer mentoring and learning services sessions.